ROBOT B-9. (From Abba to Zoom: A Pop Culture Encyclopedia of the Late 20th Century, 2005)
Information on the robot, "Robot B-9" is presented. The robot was used in the 1960s sci-fi TV series "Lost in Space". Dick Tufeld provided voice to the robot. In the TV series, the robot guided the Robinson family on their explorations in outer space.